Dunia Majapahit dalam Hikayat Hang Tuah: Kajian Sastra Perjalanan Carl Thompson - Pranatama Kesdihandaru (Sasdaya: Gadjah Mada Journal of Humanities, 2026)
This paper will discuss the depiction of the world, representation of others, and agenda in the Hikayat Hang Tuah text, episode of the journey to Majapahit. Hang Tuah's journey to Majapahit is the most significant episode narrated in the Hikayat Hang Tuah text. The author of the Hikayat Hang Tuah text not only reports on the depiction of the world in terms of landscapes and places, but also the people of Majapahit. The depiction of the world of Majapahit through the perspective of the Malay author is interesting to study because it reveals the hidden agenda within it. The Hikayat Hang Tuah text used in the field of research is the edited text by Kassim Ahmad. Meanwhile, Carl Thompson's travel literature, which focuses on world depictions, representations of others, and agendas, is the material object of this paper. This study uses a descriptive analytical method that describes facts followed by analysis and interpretation. The data in this study consists of a series of words or quotations in the form of narratives and dialogues that describe the depiction of the world, the representation of others, and the agenda. Based on the results of the analysis, it was found that the depiction of the world in the form of landscapes, places, and people is both objective and subjective. Based on the analysis of the depiction of the world and the representation of others, the agenda is revealed in the form of ethical and political implications.